Qualidade de vida de crianças e adolescentes com paralisia cerebral - Silva, Priscilla Ludovico da (2012)
Cerebral Palsy (CP) is a group of permanent disorders of tone, posture and movement, attributed to non-progressive lesions of the developing brain which causes functional limitations. The severity of the motor function can affect the quality of life (QoL), which is the individual's perception of their position in life, when it comes to culture and value system where they live. Objectives: to evaluate the parent-reported child and adolescent with CP QoL and to correlate it with the severity of motor function and social support received by caregivers in their different domains (physical, emotional, social and school). Methods: The study included 43 primary caregivers of children and adolescents 6 to 14 years of age with CP being treated at the Associação de Assistência à Criança Deficiente AACD, São Paulo. Gross Motor Function Classification System - GMFCS was used to classify gross motor function. The patients were divided into three groups of severity: mild, moderate and severe. To evaluate the QoL, the instrument used was the Pediatric Quality of Life Inventory - 4.0 PedsQLTM and to evaluate the social support of caregivers, it was used the Social Support Questionnaire - SSQ. Participants also completed a single question about the meaning of QoL. Results: There was no difference between the scores of QoL in the three groups of motor impairment, there was only difference between the scores of the physical domain, indicating that as higher the motor impairment is, the physical domain will be lower. We found that satisfaction with social support received was the same for all groups, regardless the classification by the GMFCS, eventhough the number of people to support is greater for caregivers who reported worse QoL of children and adolescents with CP in the study. The definitions of QOL given by caregivers indicate the expectation of independence as the main factor for QoL. Conclusion: The search for better QoL should be part of programs to support caregivers and persons with CP, however, this search should be the goal for the present and not only a projection for the future.